993. "I feel like they're actually listening to me": A Pilot Study of Hospital Discharge-Decision Making for Patients with Injection Drug Use-Associated Infections. (15th December 2022) - Thakarar, Kinna; Kohut, Michael R; Stoddard, Henry; Burris, Debra; Sikka, Monica K; Solomon, Daniel A; Kershaw, Colleen; Eaton, Ellen; Chessa, Frank; Hutchinson, Rebecca; Fairfield, Kathleen; Friedmann, Peter; et al.
Abstract: Background: Conversation guides have the potential to transform care for patients hospitalized with injection drug use (IDU)-associated infections. This study's objectives were to 1) pilot a structured conversation guide for hospital discharge decision making in patients with IDU-associated infections 2) investigate the guide's feasibility and acceptability and 3) examine patient and provider experiences, patient outcomes, and lessons learned. Methods: We developed a conversation guide and conducted semi-structured interviews with physicians and patients at a tertiary care center in Maine. We interviewed physicians after each piloted the guide with two patients. We interviewed patients less than one week after the conversation and again after 4-6 weeks. Two analysts indexed transcriptions and used the framework method to identify and organize relevant information. We conducted retrospective chart review to corroborate and contextualize qualitative data. Results: Eight patients and four infectious disease physicians piloted the conversation guide. All patients (N=8) completed antimicrobial treatment and 88% were discharged on medication for opioid use disorder (Table 1). All providers and most patients stated that the conversation guide was important for incorporating patient preferences and antimicrobial treatment options. Patients appreciated more autonomy and their voices being included in their care. Providers felt the guide facilitated their understanding of patient values. Values and preferences between patients and providers were aligned. Participants identified the length of the guide, discussion of pain management, and addressing post-discharge needs such as housing as areas for improvement (Table 2). Conclusion: The use of a conversation guide to inform hospital discharge decision making for patients with IDU-associated infections incorporates patient preferences and values into treatment decisions. While we identified areas for improvement, overall patients and providers believed that this novel conversation guide helped to improve patient care and autonomy. Disclosures: Kinna Thakarar, DO, MPH, Maine Medical Center: Board Member|NIH: Grant/Research Support|University of New England: Board Member Monica K. Sikka, MD, F2G: Site research investigator Ellen Eaton, MD, MSPH, Gilead: Grant/Research Support.